Association and expression study of MMP3, TGFb1 and COL10A1 as candidate genes for leg weakness-related traits in pigs - Laenoi W. (2014)
The present study was aimed to determine the association between metalloproteinase 3 (MMP3), transforming growth factor beta 1 (TGFb1) and collagen type X alpha I (COL10A1) gene polymorphisms with traits related to leg weakness in pigs. Three hundred Duroc 9 Pietrain cross breds (DuPi) and 299 pigs of a commercial population (CP) were used for the experiment. DuPi animals were examined for 10 different traits describing leg and feet structure, osteochondrosis (OC) scores and bone density status. Data of OC score at condylus medialis humeri, condylus medialis femoris and distal epiphysis ulna regions of CP were used for association analysis. Significant association (P<0.05) was found for MMP3 SNP (g.158 C>T) with OC at head of femur and bone mineral density in the DuPi population. Association (P<0.05) was found between SNP of TGFb1 (g.180 G>A) with rear leg score and the principle component denoting both OC and feet and leg scores in the DuPi population. No association was found between COL10A1 (g.72 C>T) and leg weakness related traits. The associations of SNPs with OC traits could not be confirmed in the commercial population. Expression analysis of the three candidate genes was performed to compare between healthy and OC. TGFb1 was found to be highly expressed (P<0.05) in the OC compared to healthy cartilages, but no significant different expressions were observed for MMP3 and COL10A1 genes. The present finding suggested that TGFb1 and MMP3 genes variants have an effect on some of the leg weakness related traits. © Springer Science+Business Media B.V. 2011.